O BRINCAR DA CRIANÇA NA CLÍNICA INFANTIL - Carniel, Cassiane Antunes; Dias, Andressa Da Silva; Lovato, Bruna Sampaio; Souza, Fabieli Da Silva (Salão do Conhecimento, 2017)
Trabalho desenvolvido no estágio supervisionado em Psicologia e Processos Clínicos I